Imposing Additional Criminal Sanction of Chemical Castration against Child Sexual Violence Perpetrators - Firda Yanis Hardianti; Emmilia Rusdiana (Universitas Negeri Semarang, 2022)
This paper aims to examine the fulfillment of the requirements for implementing the judge's decision Number: 69/Pid.Sus/2019/PN Mjk in providing additional punishment in the form of chemical castration and rationalization of the Indonesian Doctors Association (IDI) in approving the implementation of the decision. The results of the study indicate that the conditions for implementing the decision No. 69/Pid.Sus/2019/Pn Mjk in providing additional punishment for chemical castration has been fulfilled, because the conditions for the imposition of additional punishment in the form of chemical castration are imposed after the convict has served the principal sentence in accordance with Article 81A paragraph (1) of Law Number 17 of 2016 concerning child protection. The reason IDI is obliged to approve the implementation of Decision Number: 69/Pid.Sus/2019/PN Mjk is that when a regulation is included in the legislation, this provision is perfectly binding and must be obeyed. So, in practice, when a doctor is asked to perform chemical castration, the doctor must do so because this provision is a legal order and there is a justification for this. The decision Sus/2019/PN Mjk is when a regulation is included in the legislation, this provision is perfectly binding and must be obeyed.